Intraocular pressure changes and pain scores within 24 hours and short-term outcomes after micropulse transscleral laser therapy - Nattanan Phanvichatkul; Pukkapol Suvannachart (PLoS ONE, 2026)
Purpose To assess intraocular pressure (IOP) changes and pain scores during 24 hours and short-term outcomes after micropulse transscleral laser therapy (MP-TLT). Design Retrospective case series. Methods We reviewed eyes undergoing MP-TLT (2,000 mW; 31.3% duty cycle; 100–200 seconds) with serial IOP measurements during the first operative day, excluding those with prior cyclophotocoagulation or combined procedures. IOP and pain scores (numerical rating scale, NRS) were recorded at 1, 5, 9, 13 hours, and the following day post-procedure. Data from follow-up visits were obtained to evaluate success rates (≥30% IOP reduction or an IOP 6–18 mmHg). Mixed-effects regression and Kaplan–Meier method were used for analysis. Results This study examines 46 eyes from 40 patients, 58.7% with secondary glaucoma. The mean preoperative IOP was 40.6 mmHg. The NRS was 2.3 at the end of the procedure. The mean postoperative IOP (% reduction) and NRS values were 33.9 (16.5) mmHg and 2.4 at 1 hour, 36.1 (11.1) mmHg and 2.8 at 5 hours, 32.6 (19.7) mmHg and 1.7 at 9 hours, 29.7 mmHg (26.8) and 1.2 at 13 hours, and 24.5 (39.7) mmHg and 1.0 on the following day. The IOPs were significantly lower at all time points (p < 0.05), with the lowest mean value of 16.4 mmHg at week 1. The success rate was 80.6% at 12 months. One patient developed transient hypotony maculopathy. Conclusions MP-TLT resulted in a significant IOP reduction within 24 hours, with maximal effect at 1 week, and demonstrated favorable short-term outcomes.